Peculiarities of inclusive education of ASD children in Ukraine - Rybchenko, Larysa; Ostrovskii, Ihor (Journal of Education Culture and Society, 2020)
Despite the fact that special education in Ukraine is quite extensive and eveloped, education itself and social psychological development remain unavailable for children with ASD. The article aim is to show a model of autistic children inclusion in the educational system of Ukraine taking into account the experience of success. The investigated group consists of 20 children with ASD and 20 children with mental retardation from a boarding school aged from 8 to 9 years. The children indices were investigated according to Binet-Simon Scale for intelligence level determination, method of neuropsychological research according to Alexander Luria for psychophysical development level determination and Childhood Autism Rating Scale for autism level determination. The analysis of inclusive education implementation in the educational system of Ukraine has been conducted. The results of studies have shown that children with ASD have substantially lower indices of speech development, capacity for imitation as well as concentration of attention than children with mental retardation. Conductance of social intervention based of TEACCH therapy elements for group of children with ASD has shown their progress in indices of social interaction, emotional reaction and communication. The results obtained allow us to build a model of inclusion of children with ASD in the educational system of Ukraine. The main components of the model are considered.